Thermal expansion behaviour of squeeze-cast aluminium matrix composites reinforced with PAN- and Pitch-based carbon fibres. (2nd November 2017) - Asano, Kazunori
Abstract: Aluminium composites reinforced with the PAN- and pitch-based short carbon fibres were fabricated by squeeze casting, then the thermal expansion behaviour of the composites was investigated. Optical microscopy revealed that the fibres were in a random arrangement on the plane parallel to the pressed plane during the melt infiltration process. TEM observation and hardness test revealed that the PAN-based fibre bonds strongly with the aluminium matrix while the pitch-based fibre bonds poorly. The difference in the bonding strength affected the thermal strain response; the heating and cooling curve approximately traced the same paths during the heating-cooling cycles for the PAN-based fibre composite, while the curve did not trace the same path for the pitch-based fibre composite. The fibre-reinforcement decreased the coefficient of the thermal expansion (CTE) of matrices in the direction parallel to the pressed plane. For example, the CTE of the pure aluminium and its composite at 333 K were 23.0 and 19.0 × 10 −6 /K, respectively.